Propriedade intelectual: registros de desenho industrial como patrimônio cultural da Universidade Federal de Santa Maria - Leal, Maristela Santos (2016)
This study adds topics such as Cultural Heritage, Intellectual Property and Design. With purpose to unite and preserve the tangible and intangible assets. Aiming to analyze the situation of production projects and Industrial Design Course of products Arts and Letters Center; identify the potential for innovation at the Federal University of Santa Maria. From a universe of 226 regular students enrolled in the first half of 2016, the Industrial Design course at UFSM. Of these, 33 subjects were included in the survey sample, and the "n" equals the number of participants. The survey was conducted between June and July 2016. The results showed an ignorance of the majority of participants (49%) of how is the registration request process with the AGITTEC. Just as there was a low prevalence of project records or products (9.10%) and the prevalence of realization of projects by respondents reached (78%) of the subjects who develop projects in CDI. However, respondents show interest in proceeding records. We conclude that there is a high need for educational proposal of possibilities of records which would impact on the improvement of R & D & I UFSM and as a result the country.